Cognitive outcome is related to functional thalamo-cortical connectivity after paediatric stroke. Issue 3 (28th April 2022) - Steiner, Leonie; Federspiel, Andrea; Slavova, Nedelina; Wiest, Roland; Grunt, Sebastian; Steinlin, Maja; Everts, Regula
Abstract: The thalamus has complex connections with the cortex and is involved in various cognitive processes. Despite increasing interest in the thalamus and the underlying thalamo-cortical interaction, little is known about thalamo-cortical connections after paediatric arterial ischaemic stroke. Therefore, the aim of this study was to investigate thalamo-cortical connections and their association with cognitive performance after arterial ischaemic stroke. Twenty patients in the chronic phase after paediatric arterial ischaemic stroke (≥2 years after diagnosis, diagnosed <16 years; aged 5–23 years, mean: 15.1 years) and 20 healthy controls matched for age and sex were examined in a cross-sectional study design. Cognitive performance (selective attention, inhibition, working memory, and cognitive flexibility) was evaluated using standardized neuropsychological tests. Resting-state functional magnetic resonance imaging was used to examine functional thalamo-cortical connectivity. Lesion masks were integrated in the preprocessing pipeline to ensure that structurally damaged voxels did not influence functional connectivity analyses. Cognitive performance (selective attention, inhibition, and working memory) was significantly reduced in patients compared to controls. Network analyses revealed significantly lower thalamo-cortical connectivity for the motor, auditory, visual, default mode network, salience, left/right executive, and dorsal attention network in patients compared with controls. Interestingly, analyses additionally revealed higher thalamo-cortical connectivity in some subdivisions of the thalamus for the default mode network (medial nuclei), motor (lateral nuclei), dorsal attention (anterior nuclei), and the left executive network (posterior nuclei) in patients compared with controls. Increased and decreased thalamo-cortical connectivity strength within the same networks was, however, found in different thalamic subdivisions. Thus, alterations in thalamo-cortical connectivity strength after paediatric stroke seem to point in both directions, with stronger as well as weaker thalamo-cortical connectivity in patients compared with controls. Multivariate linear regression, with lesion size and age as covariates, revealed significant correlations between cognitive performance (selective attention, inhibition, and working memory) and the strength of thalamo-cortical connectivity in the motor, auditory, visual, default mode network, posterior default mode network, salience, left/right executive, and dorsal attention network after childhood stroke. Our data suggest that the interaction between different sub-nuclei of the thalamus and several cortical networks relates to post-stroke cognition. The variability in cognitive outcomes after paediatric stroke might partly be explained by functional thalamo-cortical connectivity strength. Abstract : The purpose of the study was to investigate resting-state thalamo-cortical connectivity and its association with cognition in patients after paediatric arterial ischaemic stroke. Steiner et al. report that the interaction between different subdivisions of the thalamus and several cortical networks might be essential for post-stroke cognitive performance. Graphical Abstract: Graphical abstract